Citizen support for European Union membership: the role of socialisation experiences - Shorrocks, R; de Geus, R (Taylor & Francis, 2019)
The article explores whether European Union membership has a socialisation effect on citizens’ attitudes towards their country’s membership of the EU. Using a sample of 15 Western European countries, it is shown that this is the case. First, evidence is provided of a positive lifelong socialisation effect: citizen support for their country’s membership of the EU increases with years spent living in an EU member state. Second, it is shown that those who joined the EU during their formative years are less supportive of the EU, whilst those who spent their formative years in a non-democracy are more positive about EU membership. The size of these effects is very small in comparison to that found for the lifelong socialisation effect, suggesting that the lifelong socialisation process of continued EU membership is much more important for EU attitudes. This study offers new insights into the formation of EU attitudes.